2014
DOI: 10.1097/lgt.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary Vulvar Paget Disease With 5% Imiquimod Cream

Abstract: On the basis of the results, the authors consider that 5% imiquimod cream could be considered a safe and effective therapeutic option for the treatment of primary vulvar Paget disease. Further studies are needed to determine the real efficacy and safety of 5% imiquimod cream for the treatment of this infrequent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Imiquimod was evaluated by 13 studies (8 cohort studies, 5 case series) in 110 patients. CR was documented in 54% of patients, and 85% achieved clinical regression of 50% or more [43][44][45][46][47][48][49][50][51][52][53][54]60]. Given the propensity of EMPD for recurrence, posttreatment histological evaluation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imiquimod was evaluated by 13 studies (8 cohort studies, 5 case series) in 110 patients. CR was documented in 54% of patients, and 85% achieved clinical regression of 50% or more [43][44][45][46][47][48][49][50][51][52][53][54]60]. Given the propensity of EMPD for recurrence, posttreatment histological evaluation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod is an immune response modifier that stimulates innate immune pathways (via induction of inflammatory cytokines, such as IFN-α, IL-6, and TNF-α) and adaptive immune pathways, resulting in an antitumor effect [59]. Eight cohort studies (3 prospective, 5 retrospective) and 5 case series (total 110 patients) investigated the effectiveness of imiquimod for EMPD at dose schedules ranging from daily to twice weekly for a duration of 2-56 weeks [43][44][45][46][47][48][49][50][51][52][53][54]60]. Overall, 54% (95% CI, 40-67%; I 2 = 37%) of patients achieved complete response (CR) and 85% (95% CI, 74-90%; I 2 = 0%) achieved clinical regression of 50% or more.…”
Section: Imiquimodmentioning
confidence: 99%
“…Most of the retrospective series have used different treatment schedules. The prospective trial of Marchitelli et al [ 35 ] used a different treatment schedule per patient. In most case studies, treatment was continued until the patient obtained a complete response.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome variable is the response at 12 weeks after end of treatment with topical 5% imiquimod cream. The only observational study on this topic, at time of conception of this trial, reported a response in 9 of 10 women [ 35 ]. Assuming a complete response rate of 80%, a cohort size of 20 patients is sufficient to estimate the complete response rate with a standard error of 9%, using the normal approximation for the binomial distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation